(untitled) (KYAMC Journal, 2013)
Existing disease pattern and health seeking behavior in a community should be known to provide need based quality service. The aim of this study was to find out the disease pattern, common diseases, age distribution, sex ratio, seasonal influence, comorbidity etc in admitted patients in Khwaja Yunus Ali Medical College & Hospital (KYAMCH), a rural tertiary care Hospital in Bangladesh. In this retrospective and descriptive study total 550 patients were evaluated in 1 year period who were admitted either from OPD or through Emergency. Most of the diagnoses were made after evaluation according to the organ system involved eg. Gastrointestinal, hepatobiliary & pancreatic (15%); Respiratory (24%); Infective (6.5%); Renal (11%); Neurological (24%); Haematological (2.75%); Endocrine (6.75%); Rheumatological (4%); Psychiatric & Poisoning (6%). Hope we will get a understanding of disease pattern among the admitted patients in a good organized way through this study. Furthermore, it will be possible to calculate the mortality, treatment success, hospital staying, total cost of treatment thus to estimate the disease burden and cost effectiveness as well. DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13261 KYAMC Journal Vol.2(2) January 2012, 172-181